2014
DOI: 10.1002/jsfa.6600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing on mycotoxin stability in cereals

Abstract: The mycotoxins that generally occur in cereals and other products are not completely destroyed during food-processing operations and can contaminate finished processed foods. The mycotoxins most usually associated with cereal grains are aflatoxins, ochratoxins, deoxynivalenol, zearalenone and fumonisins. The various food processes that may have effects on mycotoxins include cleaning, milling, brewing, cooking, baking, frying, roasting, flaking, alkaline cooking, nixtamalization, and extrusion. Most of the food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 46 publications
(88 reference statements)
4
49
0
1
Order By: Relevance
“…Our results were in accordance with previous studies (Milani & Maleki, ; Pacin et al., ; Scudamore, Hazel, Patel, & Scriven, ; Vidal et al., ). The mean reduction in DON between flour and products was 42.3% for French bread and 58.3% for Vienna bread (Pacin et al., ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results were in accordance with previous studies (Milani & Maleki, ; Pacin et al., ; Scudamore, Hazel, Patel, & Scriven, ; Vidal et al., ). The mean reduction in DON between flour and products was 42.3% for French bread and 58.3% for Vienna bread (Pacin et al., ).…”
Section: Discussionsupporting
confidence: 94%
“…The mean reduction in DON between flour and products was 42.3% for French bread and 58.3% for Vienna bread (Pacin et al., ). Milani and Maleki () reported that baking regular bread, cookies, and biscuits provided a variable DON reduction, from 24% to 71% in bread and 35% in cookies and biscuits. The mean concentrations of DON in white bread and wholemeal bread were reduced by about 35% and 39%, respectively, than the concentration in the flour (Scudamore et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of food-processing on the fate of free mycotoxins in food or feed has been extensively investigated and reviewed (Bullerman and Bianchini, 2007;Hazel and Patel, 2004;Jackson and Bullerman, 1999;Milani and Maleki, 2014;Trigo-Stockli, 2002). The (thermo)stability of trichothecenes allows them to withstand most food and feed processes (Malachova et al, 2010).…”
Section: Effects Of Food Processingmentioning
confidence: 99%
“…Moreover, model studies suggest that the mechanism of Se protection involves ZEA‐Se interactions that depend on genotype‐specific structural differences in membranes . Infection of plants by ZEA is an important agronomical problem because Fusarium fungi can be adsorbed on various plant organs (grains, roots, leaves) . When humidity is high and temperatures relatively low, as in spring in temperate climate zones, the leaves of young seedlings are especially exposed to the action of fungi.…”
Section: Introductionmentioning
confidence: 99%